Comparing Campylobacter jejuni to three other enteric pathogens in OligoMM12 mice reveals pathogen-specific host and microbiota responses - Mathias K.-M. Herzog; Audrey Peters; Nizar Shayya; Monica Cazzaniga; Kardokh Kaka Bra; Trisha Arora; Manja Barthel; Ersin Gül; Luca Maurer; Patrick Kiefer; Philipp Christen; Katharina Endhardt; et al. (Gut Microbes)
Campylobacter jejuni, non-typhoidal Salmonella spp., Listeria monocytogenes and enteropathogenic/enterohemorrhagic Escherichia coli (EPEC/EHEC) are leading causes of food-borne illness worldwide. Citrobacter rodentium has been used to model EPEC and EHEC infection in mice. The gut microbiome is well-known to affect gut colonization and host responses to many food-borne pathogens. Recent progress has established gnotobiotic mice as valuable models to study how microbiota affect the enteric infections by S. Typhimurium, C. rodentium and L. monocytogenes. However, for C. jejuni, we are still lacking a suitable gnotobiotic mouse model. Moreover, the limited comparability of data across laboratories is often negatively affected by variations between different research facilities or murine microbiotas. In this study, we applied the standardized gnotobiotic OligoMM12 microbiota mouse model and compared the infections in the same facility. We provide evidence of robust colonization and significant pathological changes in OligoMM12 mice following infection with these pathogens. Moreover, we offer insights into pathogen-specific host responses and metabolite signatures, highlighting the advantages of a standardized mouse model for direct comparisons of factors influencing the pathogenesis of major food-borne pathogens. Notably, we reveal for the first time that C. jejuni stably colonizes OligoMM12 mice, triggering inflammation. Additionally, our comparative approach successfully identifies pathogen-specific responses, including the detection of genes uniquely associated with C. jejuni infection in humans. These findings underscore the potential of the OligoMM12 model as a versatile tool for advancing our understanding of food-borne pathogen interactions.